Phage-mediated dissemination of virulence factors in pathogenic bacteria facilitated by antibiotic growth promoters in animals: a perspective. (29th November 2017) - Tamang, Migma Dorji; Sunwoo, Hoon; Jeon, Byeonghwa
Abstract: Addition of sub-therapeutic antibiotics to the feed of food-producing animals for growth promotion and disease prevention has become a common agricultural practice in many countries. The emergence of antibiotic-resistant pathogens is a looming concern associated with the use of antibiotic growth promoters (AGPs) around the world. In addition, some studies have shown that AGPs may not only affect antibiotic resistance but may also stimulate the dissemination of virulence factors via bacteriophages. Although only a few studies are currently available in the literature regarding this topic, in this article we endeavor to provide a perspective about how AGPs would impact the transmission of virulence factors by horizontal gene transfer via phages in a few pathogenic bacterial species significant to livestock production.